InCIEC 2014 2015
DOI: 10.1007/978-981-287-290-6_50
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Test Methods for Shear Strength Behavior of Unsaturated Soils Under Suction Control, Using Triaxial Apparatus

Abstract: The shear strength of an unsaturated soil is controlled by two variables; net stress and suction. The conventional triaxial machine which is used for obtaining the shear strength of saturated soils cannot be used for unsaturated soil conditions due to weakness in suction control during the consolidation and shearing stages. In the view of this, the standard triaxial apparatus needs to modify and develop for unsaturated conditions. The main aim of this paper is devoted to give a description of current methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In terms of partially saturated condition a modified double wall triaxial apparatus with suction control was used. The suction of 70 kPa (residual suction obtained from SWCC test) was applied to the specimen using axis translation technique [14]. The triaxial test has been conducted at effective stresses of 50 kPa, 100 kPa, 200 kPa and 300 kPa.…”
Section: Triaxial Test Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of partially saturated condition a modified double wall triaxial apparatus with suction control was used. The suction of 70 kPa (residual suction obtained from SWCC test) was applied to the specimen using axis translation technique [14]. The triaxial test has been conducted at effective stresses of 50 kPa, 100 kPa, 200 kPa and 300 kPa.…”
Section: Triaxial Test Resultsmentioning
confidence: 99%
“…Later on, it was reported that there is a unique relationship between the minimum mobilized friction angle, Ø' min mob , and axial strain, ε a [14] . Applying the deviator stress rotates the mobilized shear strength into a new position regardless of the value of effective or net stress in accordance with axial strain either for saturation or unsaturation condition.…”
Section: Rotational Multiple Yield Surface Framework (Rmysf)mentioning
confidence: 99%
See 1 more Smart Citation